Indonesian pre-service teachers’ changing beliefs about cognitive strategies during online English practice - Pusparini, Ririn; Ali Saukah; Widyastuti (Universitas Muhammadiyah Sidoarjo, 2025)
Technological competence remains a highly recommended skill for teachers, their beliefs about cognitive strategies can significantly influence the integration of technology in online teaching practices. This study aims to investigate the beliefs of pre-service teachers (PSTs) regarding cognitive strategies during online English teaching practices. Specifically, it explores the beliefs held by PSTs prior to their teaching practicum in schools and the subsequent changes in these beliefs during the practicum. To gain deeper insight into the nature of these beliefs, a qualitative research methodology was employed. Data were collected through semi-structuredinterviews, online classroom video observations, and questionnaires. The study involved 36 fourth-year PSTs from the Language Education Study Program at a public university in Indonesia, with 8 of them participating in the interviews and classroom observations. The findings reveal that PSTs’ beliefs about cognitive strategieschanged notably in relation to promoting communicative, problem-solving, and student-centered activities. Partial changes were observed in beliefs related to the use of learning videos, the use of the target language in class, and speech pacing. In addition, the findings indicate that changes in beliefs were largely influenced by ITinfrastructure, which affected time allocation for teaching and the selection of teaching platforms dictated by school policy. Moreover, PSTs' limited IT competencies and the lack of effective monitoring of students' activities, conditions, and behaviors were identified as key constraints shaping their beliefs during online teaching. Therefore, it is recommended that school mentors and teacher education programssupport PSTs in reshaping their beliefs, particularly in relation to online teaching practices. Moreover, teachers and students require comprehensive support from parents, schools, the government, and the broader community to achieve learning objectives and foster effective online classrooms.HIGHLIGHTS : PSTs’ beliefs about cognitive strategies changed notably in relation to promoting communicative, problem-solving, and student-centered activities. Partial changes were observed in beliefs related to the use of learning videos, the use of the target language in class, and speech pacing Changes in beliefs were largely influenced by IT infrastructure, which affected time allocation form teaching and the selection of teaching platforms dictated by school policy. PSTs’ limited IT competencies and the lack of effective monitoring of students’ activities, conditions, and behaviors were identified as key constraints shaping their beliefs during online teaching.